From Profiles to Success: Linking Founders’ Characteristics in Real Estate Startups to Entrepreneurial Success - Svensson,Johannes; Zelenka,Jan (2025)
bstract The real estate sector in Sweden has long been characterized by high entry barriers, strict regulations, and a high demand for large initial capital. These factors make it challenging for new ventures to succeed in the market. With this background, it seems relevant to understand which driving factors can be related to entrepreneurial success. This study researches how specific characteristics of founders relate to the survival of real estate startups in Sweden. The characteristics are based on the theories within social and human capital and are, in this study, listed as follows: prior industry experience, post-secondary level education, social network size, and lastly, digital engagement on the social media platform of LinkedIn. Using data from Allabolag and LinkedIn profiles, the study analyzed 100 real estate startups and founders to respond to the four hypotheses, connected to the four characteristics. The findings revealed that digital engagement through posts, comments, and reposts has a significant positive relation to business survival, suggesting that founders within the field should have a high digital presence towards their professional network. On the other hand, formal education was proven to be related to a decreased business survival, suggesting that the traditional assumptions of human capital theory might be outdated, and that there is a need for broader and practical knowledge to make entrepreneurs more adapted to the changing environment. The study contributes to the existing literature by presenting information about the strictly regulated Swedish real estate market, combined with an open media-based data source to assess founders' attributes and how they correlate to entrepreneurial success. It provides practical implications for entrepreneurs, investors, and policymakers, along with limitations of the study that can be addressed through potential future research opportunities.
Keywords: Entrepreneurial success; Real estate; Human capital; Social capital; LinkedIn; Startup survival; Digital engagement